2013
DOI: 10.1111/age.12088
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic resolution power of microsatellites and various single‐nucleotide polymorphism types assessed in 10 divergent chicken populations

Abstract: There has been some debate over the question of which types of DNA variation are most appropriate to accurately reconstruct evolutionary events. We compared the capacity of microsatellites (STRs) and various types of single-nucleotide polymorphism (SNP) loci in the chicken genome. The SNP types differ in their location: in exons, introns and promoters. Genetic distances between all possible pairs of 10 populations were calculated for each marker type. STR loci, which are much more polymorphic than are SNPs, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This result is in agreement with the conclusions of Granevitze et al (2014), who stated that microsatellite loci may perform even better than other marker types in the assignment tests applied to wild and domestic chicken populations.…”
Section: Articlesupporting
confidence: 92%
“…This result is in agreement with the conclusions of Granevitze et al (2014), who stated that microsatellite loci may perform even better than other marker types in the assignment tests applied to wild and domestic chicken populations.…”
Section: Articlesupporting
confidence: 92%
“…; Granevitze et al. ; Ross et al. ), whereas ascertainment from a larger pool improved the performance of SNPs (Glover et al.…”
Section: Introductionmentioning
confidence: 99%
“…autogamy, clonality). Guichoux et al [16] suggested that microsatellites may be better than SNP to detect mixtures of genetic clusters (see also [17, 18]. But opposite findings have also been reported and the debate on the relative performance of SNPs over SSRs remains [19].…”
Section: Introductionmentioning
confidence: 99%